„АND RHYMES ARE SHARPENED, AND HARMONIC STROPHES" - Салига, Т. Ю. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article the features of creation of Vadim Lesich are considered in the context of literature of diaspora. By the dominant of his creation an elegiac canon is certain and special „recording". Also attention appeal on the lexical features of poetry V. Lesich.